Preparation of modified SrAl1.3Fe10.7O19 nanostructures and evaluation of size influence on its optical and magnetic properties. (1st September 2020) - Peymanfar, Reza; Javidan, Abdollah; Selseleh‐Zakerin, Elnaz
Abstract : Modifying the morphology of nanostructures and its influence on the features of the tailored nanoparticles (NPs) has attracted a great deal of interest. In this research, the morphological effect on magnetic properties of the bare or modified NPs was investigated. Bare NPs were fabricated by the sol–gel route and modified NPs were prepared using hydrophilic absorbent cotton (HAC) to architect morphology of the NPs. X‐ray diffraction, field emission scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, and Fourier transform infrared analyses confirmed that pure SrAl1.3 Fe10.7 O19 NPs were synthesised based on the modified sol–gel method. Results indicated that HAC as a novel and affordable template modified the shape of the NPs. The obtained results by the diffuse reflection spectroscopy suggest that the optical performance of the NPs can be tuned by modifying the size of them. Additionally, the hysteresis loops of the vibrating sample magnetometer attested that the saturation magnetisation ( M s ) of the modified NPs was elevated.